(untitled) (Tabularium Historiae, 2019)
The purpose of the article is indication of the territorial coverage of the cup marks in the area of Romanian Transylvania. Their characteristics are presented, that is, the forms in which they appear on the facades, nomenclature, range of occurrence, views on their genesis. Against that background described objects on which the author found tthe cup marks and then these traces and their location on a given building are described.